The Shushybye Dream Band [videorecording (DVD)] Live on tour! - LaPierre, A. (WGBH Boston Video, 2005)
Get ready to clap your hands and stomp your feet to the totally cool music and rocking beat of the Shushybye Dream Band! A toe-tapping, finger-snapping concert experience for young children (and grown-ups!)